2023
DOI: 10.1039/d3nr00484h
|View full text |Cite
|
Sign up to set email alerts
|

Metal functionalization of two-dimensional nanomaterials for electrochemical carbon dioxide reduction

Abstract: With the mechanical exfoliation of graphene in 2004, researchers around the world have devoted significant efforts to the study of two-dimensional (2D) nanomaterials. Nowadays, 2D nanomaterials develop into a large...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 159 publications
(229 reference statements)
0
3
0
Order By: Relevance
“…For the precise engineering of electrocatalysts in enhancing their activity and selectivity, heteroatom incorporation into existing catalysts emerges as a practical and accessible approach. , By carefully selecting specific elements and controlling their concentrations, the introduction of additional electrons or holes allows for the fine-tuning of electronic band structure, electron density distribution, and other catalyst characteristics. , Based on the different supporting materials, it can be generally divided into doping on carbon-based substrates ,, and metal-based substrates, while the former aims to modulate the embedded metal sites, and the latter activates both the substrate and doping atoms.…”
Section: Strategies To Design Electronic Structure Of Tmcs In Co2rrmentioning
confidence: 99%
“…For the precise engineering of electrocatalysts in enhancing their activity and selectivity, heteroatom incorporation into existing catalysts emerges as a practical and accessible approach. , By carefully selecting specific elements and controlling their concentrations, the introduction of additional electrons or holes allows for the fine-tuning of electronic band structure, electron density distribution, and other catalyst characteristics. , Based on the different supporting materials, it can be generally divided into doping on carbon-based substrates ,, and metal-based substrates, while the former aims to modulate the embedded metal sites, and the latter activates both the substrate and doping atoms.…”
Section: Strategies To Design Electronic Structure Of Tmcs In Co2rrmentioning
confidence: 99%
“…Among them, GO has garnered special attention due to its large lateral size, excellent electronic conductivity, and high stability. 52 Bai et al reported a Co–Co LDH/GO composite, where GO nanosheets were initially sandwiched by ZIF-67 nanocages through facile co-deposition. 53 Subsequently, the ZIF-67 nanocages were converted into Co–Co LDH hollow nanocages via a thermal ion-exchange reaction with Co(NO 3 ) 2 ·6H 2 O.…”
Section: Various Mof-derived Ldhs For Supercapacitorsmentioning
confidence: 99%
“…Copper (Cu), a well-known metal catalyst in carbon dioxide reduction reaction (CO 2 RR), without which C-C coupling is hard to be realized to obtain high-value multi-carbon products like ethanol and ethylene, [95][96][97][98][99] is also a crucial element for NO 3 RR. [100,101] Nitrate conversion to nitrite has been discovered as a ratedetermining step of NO 3 RR, and Cu is highly effective in promoting this reaction. [51,102,103] Based on the frontier molecular orbital theory, compared with other metal elements, Cu has the highest occupied molecular orbital (HOMO, d-orbital) and simultaneously the lowest unoccupied molecular orbital (LUMO) similar to nitrate (𝜋-orbital) theoretically, meaning that Cu can easily inject electron into the N-O bond of nitrate and activate the NO 3 RR process.…”
Section: Copper-based Catalystsmentioning
confidence: 99%